The Effect of Modified Atmosphere Packaging with Oxygen, Carbondioxide, Water Vapor and Ethilene Scavenger of Barangan Banana (Musa Paradisiaca, L.) During Storage at Room Temperature - Hengky Irawan; Ismed Suhaidi; Terip Karo-Karo (Universitas Sumatera Utara, 2016)
The use of active modified atmosphere packaging can extend the shelf life of fruits. Research had been carried out using completely randomized factorial design with two factors. The first factor was the method of packaging namely active packaging each P1: carbondioxide scavenger and water vapor scavenger, P2: carbondioxide scavenger, ethylene scavenger and water vapor scavenger, P3: 4% O2 and 2% CO2, carbondioxide scavenger and ethylene scavenger, P4: oxygen scavenger, carbondioxide scavenger, ethylene scavenger, and water vapor scavenger. The second factor was storage time namely 1, 2, and 3 weeks storage. Parameter measured were weight reduction, total soluble solid, total acid content, total sugar content, hardness, water content, vitamin C content, moisture content, color scores, pulp ratio, and concentration of carbondioxide and oxygen in packaging. The results showed that the method of packaging had highly significant effect on weight reduction, total soluble solid, total acid content, total sugar content, hardness, water content and concentration of carbondioxide and oxygen. Storage time had affected all parameters. Treatment interaction had highly significant effect on weight reduction, total soluble solid, total acid content, total sugar content, hardness, and concentration of carbondioxide and oxygen. The best result obtained was in a combination of active packaging using oxygen scavenger, carbondioxide scavenger, ethylene scavenger, water vapor scavenger, stored for 3 weeks. Keywords: active packaging, barangan banana, scavenger, storage.